2020
DOI: 10.1155/2020/9105972
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of Action of Bu-Fei-Yi-Shen Formula in Treating Chronic Obstructive Pulmonary Disease Based on Network Pharmacology Analysis and Molecular Docking Validation

Abstract: Objective. To explore the mechanism of action of Bu-Fei-Yi-Shen formula (BFYSF) in treating chronic obstructive pulmonary disease (COPD) based on network pharmacology analysis and molecular docking validation. Methods. First of all, the pharmacologically active ingredients and corresponding targets in BFYSF were mined by the Traditional Chinese Medicine Systems Pharmacology (TCMSP) database, the analysis platform, and literature review. Subsequently, the COPD-related targets (including the pathogenic targets a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 61 publications
0
9
0
Order By: Relevance
“…com/). We then performed Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway enrichment analyses for the core targets and identified the key biological functions (biological processes, molecular functions, and cellular components) and related signaling pathways (Wu et al, 2020). Finally, an ingredient-target-pathway (I-T-P) network was generated by Cytoscape version 3.6.1 software, which featured a number of relationships, including the active chemical ingredients of ZSS, the core targets, and the enriched signaling pathways (An et al, 2020).…”
Section: Go and Kegg Pathway Enrichment Analysesmentioning
confidence: 99%
“…com/). We then performed Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway enrichment analyses for the core targets and identified the key biological functions (biological processes, molecular functions, and cellular components) and related signaling pathways (Wu et al, 2020). Finally, an ingredient-target-pathway (I-T-P) network was generated by Cytoscape version 3.6.1 software, which featured a number of relationships, including the active chemical ingredients of ZSS, the core targets, and the enriched signaling pathways (An et al, 2020).…”
Section: Go and Kegg Pathway Enrichment Analysesmentioning
confidence: 99%
“…In fact, BYF can treat patients with COPD via their multiple components. According to the network pharmacology analysis and molecular docking validation, a study showed that 48 components in BYF might act on 65 targets to exert the therapeutic effect, and the therapeutic process involved IL-17, Toll-like receptor (TLR) and TNF pathways ( Wu et al, 2020 ). Therefore, more attention should be drawn to BYF for therapeutic use in COPD.…”
Section: Prevention and Present Treatmentmentioning
confidence: 99%
“…Nonetheless, certain limitations should be noted in the present work [66], like the data-based network pharmacology, which made it impossible to examine whether all data were comprehensively collected and whether the criteria to select core components were completely accurate. Besides, the efficacy of additional components and effects of dosage should be further examined.…”
Section: Discussionmentioning
confidence: 95%